Exploring the relationship between air quality and health shocks to the elderly: A retrospective cross-sectional study in China - Li, Xinyu; Lyu, Yanxia; Dong, Wanyue; Xu, Aijun (Frontiers in Public Health, 2023)
Methods We selected 5,172 microdata on individuals from the China Health and Retirement Longitudinal Study (CHARLS) 2018. The binary logit model, the ordered logit model, and the stepwise regression were employed to compare the effects of air pollution on self-rated health (SRH) and activities of daily living (ADL) in an elderly population. The effects on health shocks were explored in different age groups, different gender groups, different regions and different sources of pollutants, respectively. Results We found that air pollution significantly increased the risk of health shocks in the elderly population, especially in the 60–69 year age group, and the eastern/central region, where NO2 and O3 were important pollutant sources. Conclusion Targeted management of the environment is necessary to improve the health status of China's elderly population. In addition, paying attention to the health status of vulnerable populations is needed to achieve social equity.